(untitled) (REMUNOM, 2026)
The social determinants of health constitute a fundamental approach to understanding how social, economic, and territorial factors contribute to the production of health inequalities observed in populations. In Brazil, differences related to income, living conditions, and access to public services directly influence the distribution of health problems and the organization of healthcare provision. The territory materially expresses these inequalities, concentrating distinct contexts of exposure to health risks and access to social resources. Given this scenario, this study aims to analyze the relationship between the social determinants of health and territorial vulnerability, considering the spatial distribution of the disease burden and the organization of public service provision. To this end, an investigation was developed based on the theoretical analysis of scientific productions that discuss social inequalities, territorial organization, and the distribution of health problems. The discussion shows that socioeconomic and territorial differences influence the occurrence of diseases, the use of health services, and the availability of healthcare resources, producing unequal patterns of morbidity and mortality among regions and social groups. Incorporating spatial analysis into public health research allows for the identification of areas with a higher concentration of health problems and an understanding of how social and territorial conditions contribute to shaping these patterns. Understanding these relationships helps strengthen health planning and formulate public policies guided by equity in the organization of services and the distribution of resources within the health system.